A review of transmission line systems under downburst wind loads. Issue 179 (August 2018) - Abd-Elaal, El-Sayed; Mills, Julie E.; Ma, Xing
Abstract: Outages of power due to transmission tower failures can cause social and economic disasters. Investigations of transmission line failures around the world have recorded that they are generally from high intensity winds from downbursts and tornadoes. Downbursts represent the greatest threat due to the extreme and extended wind events that they generate. Many studies have investigated the applications of these events on transmission line systems (TLS). However, the wide ranges for the different downburst parameters and the varying representations of downburst wind speeds, which are different from boundary layer wind profiles, have complicated the investigation of transmission line failures under these types of loads. This study reviews the research to date on TLS under downburst wind loads. It explores downburst wind loads, their simulation models and the structural behaviour of TLS under downburst wind loads. Modelling of TLS, static and dynamic analysis are all reviewed. Failure analysis, critical downburst parameters, ideal retrofitting methods to avoid such catastrophic failures, and optimization criteria of TLS are also discussed. Finally, recommendations for future research are made. Highlights: A review of the research to date on downburst wind loads and ways of simulating. Modelling of transmission line systems under downburst wind events has been reviewed. Retrofitting techniques for transmission line systems, further developments and new applications have been suggested. Recommendations for further research of transmission line systems under downburst wind speeds.